Synthesis of Solid-phase Supported Chiral Amines and Investigation of Stereoselectivity of Aldol Reactions of Amine-free Tropinone Enolate - Nodzewska, Aneta; Wadolowska, Agnieszka; Podgorska, Katarzyna; Pawelski, Damian; Lazny, Ryszard (Current Organic Chemistry, 2019)
Seven selected chiral mono-, di-, and tridentate amines supported on insoluble polymer were effectively prepared from corresponding primary amines or secondary amino alcohols and Merrifield resin. The reaction of the polymer-supported amines with excess n-butyllithium gave the corresponding lithium amide bases, which were tested in the aldol reactions of tropinone with benzaldehyde. The deprotonation reactions were carried out with or without separation of the lithium enolate from polymer-supported reagents. Using the procedure with separation of lithium enolate from supported chiral reagent different results were obtained with or without the addition of LiCl despite the fact that aggregate formation of Merrifield resin supported Li-amides is hindered. Without the additive, the aldol products were obtained in low diastereoselectivity and enantioselectivity, whereas the addition of LiCl resulted in a significant increase of de and ee even when LiCl was added after the deprotonation step and separation of the chiral amine.
Keywords: chiral lithium amide